What Comes First: Return to School or Return to Activity for Youth After Concussion? Maybe We Don't Have to Choose - DeMatteo, Carol A.; Randall, Sarah; Lin, Chia-Yu A.; Claridge, Everett A. (Frontiers in Neurology, 2019)
Objectives: Return to School (RTS) and Return to Activity/Play (RTA) protocols are important in concussion management. Debate exists as to sequence and whether progression can occur simultaneously. Experts recommend that children/youth fully return to school, before beginning RTA protocols. This study investigates recovery trajectories of children/youth while following RTA and RTS protocols simultaneously, with the following objectives: 1) compare rates of progression through the stages of both protocols; 2) compare symptom trajectories during protocol progression; 3) determine if integration of RTS and RTA protocols can occur concurrently without interrupting recovery trajectories. Methods: In a 3-year prospective-cohort study of 139 children/youth aged 5-18 years with concussive injury, self-reported symptoms using PCSS and stage of protocols were evaluated every 48 hours using electronic surveys until full return to school and activity/sport were attained. Information regarding school accommodation and achievement was collected. Results: Sample mean age is 13 years, 45% male. Youth are returning to school with accommodations significantly quicker than RTA (p=.001). Significant negative correlations between total PCSS score and stage of RTS protocol were found at: one-week (r=-0.376, p<0.0001; r=-0.317, p=0.0003), one-month (r=-0.483, p<0.0001; r=-0.555, p<0.0001) and three-months (r=-0.598, p<0.0001; r=-0.617, p<0.0001); indicating lower symptom scores correlated with higher guideline stages. Median full return to school time is 35 days with 21% of youth symptomatic at full return. Median return time to full sport competition is 39.5 days with 15% still symptomatic. Sixty-four percent of youth reported experiencing school problems during recovery and 30% at symptom resolution, with 31% reporting a drop in their grades during recovery and 18% at study completion. Conclusion: Children/youth return to school faster than they return to play despite symptom profiles. Youth can progress simultaneously through the RTS and RTA protocols during stages 1-3. Considering the numbers of youth having school difficulties post-concussion, full contact sport, stage 6, of RTA, should be delayed until full and successful reintegration back to school has been achieved. In light of the huge variability in recovery, balancing symptoms with cognitive and physical demands is still the challenge for each individual child, warranting further research.